Establishment and Maintenance of Long-Term Murine Gammaherpesvirus 68 Latency in B Cells in the Absence of CD40 - Willer, David O. (American Society for Microbiology, 2005)
Murine gammaherpesvirus 68 (γHV68), like Epstein-Barr virus (EBV), establishes a chronic infection in its host by gaining access to the memory B-cell reservoir, where it persists undetected by the host's immune system. EBV encodes a membrane protein, LMP1, that appears to function as a constitutively active CD40 receptor, and is hypothesized to play a central role in EBV-driven differentiation of infected naive B cells to a memory B-cell phenotype. However, it has recently been shown that there is a critical role for CD40-CD40L interaction in B-cell immortalization by EBV (K.-I. Imadome, M. Shirakata, N. Shimizu, S. Nonoyama, and Y. Yamanashi, Proc. Natl. Acad. Sci. USA 100:7836-7840, 2003), indicating that LMP1 does not adequately recapitulate all of the necessary functions of CD40. The role of CD40 receptor expression on B cells for the establishment and maintenance of γHV68 latency is unclear. Data previously obtained with a competition model, demonstrated that in the face of CD40-sufficient B cells, γHV68 latency in CD40-deficient B cells waned over time in chimeric mice (I.-J. Kim, E. Flano, D. L. Woodland, F. E. Lund, T. D. Randall, and M. A. Blackman, J. Immunol. 171:886-892, 2003). To further investigate the role of CD40 in γHV68 latency in vivo, we have characterized the infection of CD40 knockout (CD40(−/−)) mice. Here we report that, consistent with previous observations, γHV68 efficiently established a latent infection in B cells of CD40(−/−) mice. Notably, unlike the infection of normal C57BL/6 mice, significant ex vivo reactivation from splenocytes harvested from infected CD40(−/−) mice 42 days postinfection was observed. In addition, in contrast to γHV68 infection of C57BL/6 mice, the frequency of infected naive B cells remained fairly stable over a 3-month period postinfection. Furthermore, a slightly higher frequency of γHV68 infection was observed in immunoglobulin D (IgD)-negative B cells, which was stably maintained over a period of 3 months postinfection. The presence of virus in IgD-negative B cells indicates that γHV68 may either directly infect memory B cells present in CD40(−/−) mice or be capable of driving differentiation of naive CD40(−/−) B cells. A possible explanation for the apparent discrepancy between the failure of γHV68 latency to be maintained in CD40-deficient B cells in the presence of CD40-sufficient B cells and the stable maintenance of γHV68 B-cell latency in CD40(−/−) mice came from examining virus replication in the lungs of infected CD40(−/−) mice, where we observed significantly higher levels of virus replication at late times postinfection compared to those in infected C57BL/6 mice. Taken together, these findings are consistent with a model in which chronic virus infection of CD40(−/−) mice is maintained through virus reactivation in the lungs and reseeding of latency reservoirs.